1994
DOI: 10.1073/pnas.91.9.3725
|View full text |Cite
|
Sign up to set email alerts
|

UV photoelectron and ab initio quantum mechanical characterization of valence electrons in Na(+)-water-2'-deoxyguanosine 5'-phosphate clusters: electronic influences on DNA alkylation by methylating and ethylating carcinogens.

Abstract: UV photoelectron data for 1,9-dImethylguanine, 3-hydroxytetrahydrofuran, and water, and results from ab initio self-consistent field (SCF) and post-SCF molecular orbital calculations were employed to describe valence electrons in clusters of 2'-deoxyguanosine 5'-phosphate (5'-dGMP-) with four water molecules and a phosphate-bound sodium ion. Two clusters (A and B) were ex . In A, Na+ is coordinated to 5'-dGMP-. In B, Na+ and 5'-dGMP-are separated by water. In 5'-dGMP-clusters, the nucleotide valence ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…These polymerases likely bypass 3-methyladenine (3-meA; [1], [19], [20], [21], [33], [34]), a prevalent alkylation lesion that persists on the DNA and brings about replication fork stalling and cell death [20], [21], [35], [36]. Indeed, E. coli strains lacking the dinB gene ( ΔdinB ) are sensitive to several alkylating agents, such as methyl methanesulfonate (MMS; [19]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polymerases likely bypass 3-methyladenine (3-meA; [1], [19], [20], [21], [33], [34]), a prevalent alkylation lesion that persists on the DNA and brings about replication fork stalling and cell death [20], [21], [35], [36]. Indeed, E. coli strains lacking the dinB gene ( ΔdinB ) are sensitive to several alkylating agents, such as methyl methanesulfonate (MMS; [19]).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that base excision repair pathways are the primary cellular response to alkylation damage [1] , [28] , [29] , [30] , [31] , [32] , though Y family DNA polymerases are also part of this response [1] , [19] , [20] , [21] . These polymerases likely bypass 3-methyladenine (3-meA; [1] , [19] , [20] , [21] , [33] , [34] ), a prevalent alkylation lesion that persists on the DNA and brings about replication fork stalling and cell death [20] , [21] , [35] , [36] . Indeed, E. coli strains lacking the dinB gene ( ΔdinB ) are sensitive to several alkylating agents, such as methyl methanesulfonate (MMS; [19] ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier investigations of mononucleotide ionization potentials 1,2,10-13,15 indicated that at the SCF level the upper occupied orbitals are largely localized on either the base, sugar, or phosphate groups. The combined theoretical and experimental method employed in evaluating nucleotide gas-phase IPs exploited this finding and the observation that SCF calculations describe differences in IPs caused by changes in structure more accurately than they provide absolute values of ionization energies. ,,, To examine the energetics of DNA ionization in the most useful way, it is important to recognize that in physiological surroundings DNA interacts with water, counterions, and protein. , Interactions with water and small counterions, like Na + , generally occur dynamically 18 on a time scale of pico- to nanoseconds. 18a,b, Results from investigations of isolated nucleotide−water−counterion clusters, in fixed geometries based on crystallographic data and in geometries that molecular dynamics calculations indicate are statistically significant, demonstrate that counterion electrostatic interactions significantly increase nucleotide IPs. ,,, For example, the lowest energy base IP in the isolated gas-phase nucleotide, 5‘-dGMP - , is approximately 1.8 eV smaller than that of 5‘-dGMP - in a gas-phase cluster in which the phosphate group interacts with an Na + ion through a single H 2 O solvation shell …”
Section: Introductionmentioning
confidence: 99%
“…Klopman et al attempted, with limited success, to relate the alkylation patterns to effects of base stacking on reaction potentials (42). Another approach to the question was proposed by LeBreton who tried to relate reactivity at different G's to an increase in p polarizability in the highest HOMO of G that reduces the transition state activation involving charge transfer (43)(44)(45). It was calculated that the ionization potential of G, which has the lowest ionization potential of the nucleobases, is decreased when it is in the interior of a hyper-reactive G 3-4 stretch.…”
Section: Sequence Selective Reactions Of Alkylating Agents With Dnamentioning
confidence: 99%